Merajut Kemaslahatan Ekonomi Dalam Perspektif Al-Qur’an - Zulfikar, Eko (Jurnal Ulunnuha, 2021)
In the world of economy, the efforts made by humans to fulfill the necessities of life certainly involve other parties. So that the operational behavior of assets arises not only for personal interests, but also includes the benefit of the people (social). This paper seeks to introduce how benefit is in the economy as far as the Qur'an sees it. By using the thematic interpretation method, it is concluded that there are at least six economic benefits in the Qur'an that must be guided by at least six, namely; economic activities are not illegal in nature, optimize natural resources, carry out equitable distribution, do not abuse one another, must have balance and simplicity, and consume something that is lawful and thayyib. These six ways of knitting economic benefit are expected to be able to become basic guidelines as well as a stepping stone in accordance with the normativity of the Koran in order to carry out all economic activities, so that disparities and insecurity can be minimized.